2020
DOI: 10.4085/1062-6050-0505.20
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond the State Law: Investigating High School Sport-Related Concussion Protocols

Abstract: Context: State laws provide general guidelines for sport-related concussion (SRC) management, but do not comprehensively address the multiple layers of management for this complex injury. While high schools are encouraged to develop a SRC protocol that includes both state law tenets and additional management practices, the execution of this warrants examination. Objective: To investigate state law compliance and practice components included in high school SRC protocols, and determine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This is supported by a study of concussion management protocols across Pennsylvania, reporting that schools with full-time AT coverage had significantly more SRC protocol components than those with part-time ATs. 3 Contextually, disparities in protocol development, implementation, and review may extend beyond AT access. For example, 72% of ATs reported that they had a team physician assigned to their school, however, only 51% had a policy and procedures manual that was developed and reviewed by their team physician, which varied by residential area (urban, suburban, rural) and school distinction (public, private).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a study of concussion management protocols across Pennsylvania, reporting that schools with full-time AT coverage had significantly more SRC protocol components than those with part-time ATs. 3 Contextually, disparities in protocol development, implementation, and review may extend beyond AT access. For example, 72% of ATs reported that they had a team physician assigned to their school, however, only 51% had a policy and procedures manual that was developed and reviewed by their team physician, which varied by residential area (urban, suburban, rural) and school distinction (public, private).…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers noted that even in the most thorough protocols, there was no follow up for long term symptoms that would be indicative of post-concussion syndrome. This would include documentation of headaches, vestibular dysfunction, sensory sensitivity, and cognitive impairments following a concussion (Beidler et al, 2022). As anticipated, it was concluded that high school concussion protocols are inadequate.…”
Section: Misidentificationmentioning
confidence: 95%
“…Through the study, they discovered that the most effective high school guidelines addressed Pennsylvania state law, included advice for injury prevention and post injury procedure, and included penalties for coaches who did not follow procedure. It also uncovered that schools with access to at least one Volume 12 Issue 2 (2023) ISSN: 2167ISSN: -1907 www.JSR.org athletic trainer were more likely to identify concussions early on, as well as follow procedure (Beidler et al, 2022). This led to better and more timely treatment, and thus a quicker recovery.…”
Section: Misidentificationmentioning
confidence: 99%
See 1 more Smart Citation
“…At local, national, and international levels, policies and laws to promote brain injury prevention should be strengthened; such steps might include harmonized road safety regulations, 46 modifications to rules of contact sports and education around risks of brain injury, 47 48 49 50 51 52 53 54 increased research and monitoring of brain-injury risk factors and incidence, and multilevel educational programs to raise awareness of causes, consequences, and optimal responses to brain injury. 55 56 57 58 59 Integrated case management and preventative strategies for individuals at risk of being undomiciled or socially excluded are also needed, as these populations might be at higher risk of brain injury when housing remains unstable.…”
Section: Preinjury Phasementioning
confidence: 99%